Nutritional care for children with feeding difficulties and disabilities: A scoping review. - Alyssa Klein; Malia Uyehara; Andrew Cunningham; Madina Olomi; Kristen Cashin; Catherine M Kirk (PLOS Global Public Health)
One billion people worldwide have a disability, and 80 percent of them live in low- and middle-income countries (LMICs). The prevalence of feeding difficulties globally ranges from 25-45 percent to 33-80 percent in children without and with disabilities, respectively. The U.S. Agency for International Development's (USAID) flagship multi-sectoral nutrition project, USAID Advancing Nutrition, conducted a scoping review of programs supporting nutritional care of children with disability and non-disability related feeding difficulties. The non-systematic scoping review included a desk review of peer-reviewed and non-peer-reviewed literature and key informant interviews. In all, 127 documents with publication dates ranging from 2003 to 2022 were identified through keyword searches and snowballing and met the inclusion criteria, and 42 experts in nutrition and disability were interviewed. Findings were organized using structured matrices of challenges and opportunities across the universal progressive model of care framework in the identification and management of feeding difficulties and disabilities and support for children with feeding difficulties and disabilities and their families. The review found insufficient policies, programs, and evidence to support children with feeding difficulties and disabilities and their families. While some resources and promising approaches exist, they are not standardized or universally used, staff are not trained to use them, and there is insufficient funding to implement them. The combination of challenges in identifying feeding difficulties and disabilities, a lack of understanding of the link between disabilities and feeding, and weak or nonexistent referral or specialized services puts these children at risk of malnutrition. Additionally, their families face challenges providing the care they need, including coping with high care demands, accessing support, obtaining appropriate foods, and managing stigma. Four areas of recommendations emerged to support children with feeding difficulties and disabilities: (1) Strengthen systems to improve identification and service provision; (2) Provide direct support to families to address determinants that affect nutrition outcomes; (3) Conduct advocacy to raise awareness of the needs and opportunities; and (4) Build the evidence base on effective interventions to identify and support these children and their families.